Oral manifestations in patients and dogs with mucopolysaccharidosis Type VII - Piranit N. Kantaputra (2019)
© 2019 Wiley Periodicals, Inc. Mucopolysaccharidosis Type VII (MPS7, also called β-glucuronidase deficiency or Sly syndrome; MIM 253220) is an extremely rare autosomal recessive lysosomal storage disease, caused by mutations in the GUSB gene. β-glucuronidase (GUSB) is a lysosomal hydrolase involved in the stepwise degradation of glucuronic acid-containing glycosaminoglycans (GAGs). Patients affected with MPS VII are not able to completely degrade glucuronic acid-containing GAGs, including chondroitin 4-sulfate, chondroitin 6-sulfate, dermatan sulfate, and heparan sulfate. The accumulation of these GAGs in lysosomes of various tissues leads to cellular and organ dysfunctions. Characteristic features of MPS VII include short stature, macrocephaly, hirsutism, coarse facies, hearing loss, cloudy cornea, short neck, valvular cardiac defects, hepatosplenomegaly, and dysostosis multiplex. Oral manifestations in patients affected with MPS VII have never been reported. Oral manifestations observed in three patients consist of wide root canal spaces, taurodontism, hyperplastic dental follicles, malposition of unerupted permanent molars, and failure of tooth eruption with malformed roots. The unusual skeletal features of the patients include maxillary hypoplasia, hypoplastic midface, long mandibular length, mandibular prognathism, hypoplastic and aplastic mandibular condyles, absence of the dens of the second cervical vertebra, and erosion of the cortex of the lower border of mandibles. Dogs affected with MPS VII had anterior and posterior open bite, maxillary hypoplasia, premolar crowding, and mandibular prognathism. Unlike patients with MPS VII, the dogs had unremarkable mandibular condyles. This is the first report of oral manifestations in patients affected with MPS VII.